Post-Heat Treatment and Mechanical Assessment of Polyvinyl Alcohol Nanofiber Sheet Fabricated by Electrospinning Technique - Mahir Es-saheb; Ahmed Elzatahry (International Journal of Polymer Science)
Polyvinyl alcohol (PVA) sheets based nanofibers were produced by electrospinning technique. Postheat treatment of the produced PVA sheets with temperatures both below and above Tg to improve the mechanical properties of this material is conducted. The morphology, microstructures, and thermal degradation of the nanofibers sheets produced were investigated using scanning electron microscopy (SEM), transmission electron microscope (TEM), and thermal gravimetric analysis (TGA). Produced nanofibers are compact, and entangled with each other, with diameters from around 150 to 210. Some mechanical characteristics of the successfully produced PVA sheets, and heat-treated, are then conducted and assessed employing uniaxial tensile tests at different speeds ranging from 1 mm/min to 100 mm/min. The tensile test results obtained show that the PVA sheets are strain rate sensitive with increasing strength as the speed (i.e., strain rate) increases. The yield tensile stress ranges from 2.411 to 6.981 MPa, the ductility (i.e., elongation percent) from ∼21 to 60%, and Young modulus ranges from 103 to 0.137 KPa. However, for heat-treated samples, it is found that the yield strength increases almost by ∼35–40% more than the values of untreated cases with values reaching up to about 3.627–9.63 MPa.